The scope of the employee’s right to permissible public criticism of the supervisor. Gloss to the judgment of the Supreme Court of 28 August 2013, I PK 48/13. critical voice - Kobroń-Gąsiorowska, Łucja (Review of European and Comparative Law, 2023)
This gloss discusses the position of the Supreme Court adopted in the judgment of August 28, 2013, I PK 48/13. The main thesis of the Court concerned the employee’s possibility of allowed public criticism of the supervisor, i.e. the right to whistleblowing, which is the disclosure of irregularities in the functioning of the workplace consisting in various types of acts of dishonesty, unfairness involving the employer or its representatives, when this does not lead to a breach of the employee’s duties consisting, in particular, in caring for the interests of the workplace and maintaining the confidentiality of information, the disclosure of which could cause damage to the employer (duty of loyalty; not to infringe the employer’s interests – Article 100 § 2 (4) of the Polish Labor Code. The Supreme Court’s lack of consistency in its ruling between informing the public about irregularities in the workplace and the employee’s duty of loyalty provides for even more doubts on the part of employees wishing to report irregularities. In the author’s opinion, the position taken in the case does not explain when loyalty is binding on the employee. The Supreme Court duplicated the lack of consistency in subsequent rulings, e.g. of May 10, 2018.